2007
DOI: 10.1111/j.1365-2249.2007.03487.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to deamidated gliadin peptide show high specificity and parallel antibodies to tissue transglutaminase in developing coeliac disease

Abstract: SummaryCoeliac disease (CD) is an enteropathy induced in genetically susceptible individuals by gluten components, gliadin, hordein and secalin, polypeptides present in cereals such as wheat, barley and rye, respectively. Although the disease starts as intolerance to gliadins, antibodies to tissue transglutaminase (tTG) in the gut epithelium are characteristic of the disease. Whereas serum autoantibodies against tTG (tTGA) are highly specific for CD, antibodies to gliadin are less informative as they can also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 25 publications
6
32
0
1
Order By: Relevance
“…The use of deamidated gliadin peptides-based ELISA (DGP-AGA) could be useful in patient diagnosis and follow-up [21]. Although there are no population-based studies on the employment of DGP-AGA, recent data from various tertiary clinics have shown DGP-AGA sensitivity and specificity comparable to tTGA [23][24][25] and anti-actin antibodies assays [26], higher than those of AGA assay [23,25]. In particular, Liu et al [27] demonstrated the usefulness of DGP-AGA in early diagnosis of children affected by CD, because antibodies against deamidated gliadin seem to appear before tTGA.…”
Section: Discussionmentioning
confidence: 98%
“…The use of deamidated gliadin peptides-based ELISA (DGP-AGA) could be useful in patient diagnosis and follow-up [21]. Although there are no population-based studies on the employment of DGP-AGA, recent data from various tertiary clinics have shown DGP-AGA sensitivity and specificity comparable to tTGA [23][24][25] and anti-actin antibodies assays [26], higher than those of AGA assay [23,25]. In particular, Liu et al [27] demonstrated the usefulness of DGP-AGA in early diagnosis of children affected by CD, because antibodies against deamidated gliadin seem to appear before tTGA.…”
Section: Discussionmentioning
confidence: 98%
“…The reason for the false positivity in these clinical conditions is not known, but it is possible that increased absorption of gluten or of its peptide fragments can be followed by a humoral immune response to the non-self antigen. The diagnostic accuracy of serum antibodies directed against deamidated gliadin seems to be higher [ 31 ], a recent fi nding that requires further confi rmation. The determination of IgG anti-tTG is useful in patients with selective IgA defi ciency (serum IgA < 5 mg/dL), but this condition should be kept separate from transient IgA defi ciency, a developmental and transient condition that is typical of infants and does not affect the possibility of an IgA-based antibody response.…”
Section: Serologic Testsmentioning
confidence: 94%
“…5 Antibodies to deamidated gliadin peptides (DGP-AGA) have recently been introduced into the wide spectrum of serologic tests for CD. [6][7][8][9][10][11][12] tTG selectively deamidates gliadin peptides by eliciting a strongly enhanced T-cell stimulatory activity, which plays a pivotal role in the development of the intestinal lesions. 13 DGP display more specific CD B-cell epitopes than the native nondeamidated peptides that are the target antigens of AGA.…”
mentioning
confidence: 99%